Calcareous nannofossil biostratigraphy from Los Molles Formation (Early to Middle Jurassic) at Barda Colorada and Puesto Touquet wells, Neuquén Basin, Argentina - Chaumeil Rodríguez, Micaela (2023)
Calcareous nannofossils from the Los Molles Formation in Barda Colorada Este x-1 (YPF.Nq.BCE.x-1) and Puesto Touquet x-2 (YPF.Nq.PTU.x-2) wells were studied. These wells are located in the central-eastern area of the Huincul High in the Neuquén Basin, where the Los Molles Formation is very well developed in the subsurface. The aim of this study is to characterize the nannofossil assemblages applying a local biostratigraphic scheme obtained in previous outcrop studies (Chaumeil Rodríguez 2023), and integrate the biostratigraphy on a seismic framework to correlate both wells. A total of 111 samples, including cuttings and cores, were prepared with standard techniques, and analyzed.